2004
DOI: 10.3141/1891-19
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulus Testing of Asphalt Concrete in Indirect Tension Mode

Abstract: This study presents the results from an analytical and experimental study on the dynamic modulus testing of hot-mix asphalt using the indirect tension (IDT) mode. An analytical solution for the dynamic modulus in the IDT mode was developed with the use of linear viscoelasticity. To verify the analytical solution, temperature and frequency sweep tests were conducted on 12 asphalt mixtures commonly used in North Carolina; both axial compression and IDT test methods were used. A modified dynamic modulus test prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 1 publication
5
57
0
1
Order By: Relevance
“…Garcia and Thompson [26] concluded that good agreement and similar accuracy dynamic modulus obtained from laboratory test. Similarly, Kim, Seo and Momen [27] also reported a good agreement and similar accuracy of dynamic modulus master curves, and shift factor are obtained from laboratory test.…”
Section: B Effect Of Polymer Modifierssupporting
confidence: 71%
“…Garcia and Thompson [26] concluded that good agreement and similar accuracy dynamic modulus obtained from laboratory test. Similarly, Kim, Seo and Momen [27] also reported a good agreement and similar accuracy of dynamic modulus master curves, and shift factor are obtained from laboratory test.…”
Section: B Effect Of Polymer Modifierssupporting
confidence: 71%
“…Foram utilizados TMNs de at茅 1/3 do di芒metro das amostras de MAF (12mm). Este fator foi proposto por Kim et al (2004) a fim de se obter uma amostra representativa. A Tabela 2 apresenta os resultados das dosagens realizadas para as tr锚s MAFs avaliadas nesse trabalho.…”
Section: Dosagem Das Mafsunclassified
“…For dynamic modulus characterization of HMAs, it is important to understand the principle of time-temperature superposition (Chehab et al, 2002;Kim et al, 2004). Simply stated, the same modulus value of a material can be obtained both at low test temperatures and long times (slow frequencies) or at high test temperatures but short times (fast frequencies).…”
Section: Time-temperature Superpositionmentioning
confidence: 98%